2002
DOI: 10.1038/sj.cdd.4400930
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis coincident with the differentiation of skeletal myoblasts is delayed by caspase 3 inhibition and abrogated by MEK-independent constitutive Ras signaling

Abstract: We demonstrate that during 23A2 skeletal myoblast differentiation, between 30-35% of the population apoptose. Both differentiation and apoptosis are controlled by the variables of cell density and time and these variables are inversely related. In response to conditions that permit both differentiation and apoptosis of parental 23A2 myoblasts, myoblasts rendered differentiation-defective by constitutive Ras signaling (A2:H-Ras myoblasts) do not apoptose. This is not merely a consequence of their differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…Caspase 3 and caspase 7 activity generally increased over time, as expected (Dee et al, 2002). However, further increased caspase activity was measured at 36 and 38 h post transduction in myoblasts expressing DUX4, and in those expressing tMALDUX4–VP16 at 38 h (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Caspase 3 and caspase 7 activity generally increased over time, as expected (Dee et al, 2002). However, further increased caspase activity was measured at 36 and 38 h post transduction in myoblasts expressing DUX4, and in those expressing tMALDUX4–VP16 at 38 h (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The growth of 10T1/2 fibroblasts and ER-MyoD:10T1/2 fibroblasts, as well as the growth and differentiation properties 23A2 myoblasts and 23A2 myoblasts silenced for MyoD expression, have been reported previously [11, 16, 21]. …”
Section: Methodsmentioning
confidence: 73%
“…We have previously reported that differentiation and apoptosis in response to culture in differentiation media (DM) are separable events in skeletal myoblasts, thus indicating the requirement for distinct signaling molecules [11]. We further determined that increased expression of the pro-apoptotic Bcl 2 family member PUMA was required for, and distinct to, the process of apoptosis in skeletal myoblasts [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These Pax7 + /MyoD - cells are thought to maintain a small pool of muscle stem cells, from which future proliferative myoblasts may be derived. Cells that escape differentiation and that fail to return to quiescence undergo apoptosis [5,6]. Indeed, apoptosis is normally regarded as a natural part of differentiation, and identifying factors involved in cell cycle control and survival undoubtedly play an important role in our general understanding of myogenesis and in the etiology of many muscle degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%